Growth Kinetics of Copper Replacement Deposition on Al and Al-Si from a Deep Eutectic Solvent. Issue 10 (23rd July 2015) - Kang, Ruixue; Liang, Jun; Qiao, Zhuhui; Peng, Zhenjun
Abstract : The galvanic replacement deposition of copper (Cu) layers from a choline chloride-ethylene glycol deep eutectic solvent was carried out on pure Al (99.99%) and Al-5Si alloy (Al-5 wt% Si alloy). The growth kinetics of Cu galvanic replacement were investigated by open circuit potential (OCP) and electrochemical noise (ECN). The microstructure characteristics of Cu layers were studied by scanning electron microscopy (SEM) and energy dispersive X-ray (EDS) analysis. Results showed that the driving force of Cu galvanic replacement deposition on Al-5Si alloy was weaker than that on pure Al substrate, resulting in the lower galvanic replacement rate of Cu on Al-5Si alloy. The Cu layer on Al-5Si alloy was dense and uniform, while was loose and discontinuous on pure Al. The Si as solid solute in Al matrix of Al-5Si alloy was the main reason for obtaining dense and uniform Cu layer on the substrate.